Impacts of Double V-Rings in the Heat Exchanger Duct on Heat Transfer and Flow Behaviors: A Numerical Study. (7th October 2021) - Boonloi, Amnart; Jedsadaratanachai, Withada
Abstract : The impacts of the double V-rings (DVR) in the heat exchanger duct (HED) on heat transfer and flow structures are numerically analyzed. The general configuration of the DVR is called "type I, " while the discrete DVR can be split into two structures, which are called "types II and III." The influences of the DVR sizes, DVR types and flow directions on heat transfer rate, friction loss, and thermohydraulic performance are considered. The Reynolds numbers in the range around 100–2000 (laminar regime at the entrance condition) are selected for the present investigation. The numerical problem of the HED installed with the DVR is solved with the finite volume method (a commercial code). The flow structure, heat transfer mechanism, and performance analysis in the HED that fitted the DVR are reported. The flow and heat transfer profiles in the HED fitted with the DVR are an important knowledge to develop the thermohydraulic performance of compact heat exchangers. As the numerical results, it is seen that the heat transfer ability of the tested duct improves around 1.05–16.62 times upper than the smooth duct. Additionally, the greatest value of the thermal enhancement factor in the HED fitted with the DVR is seen to be around 4.17 at a / H = 0.025, b / H = 0.10, Re = 2000, and V-upstream direction for the type I.